Рецензія: Paul Srodecki. Antemurale Christianitatis. Zur Genese der Bollwerksrhetoric im östlichen Mitteleuropa an der Schwelle vom Mittelalter zur Frühen Neuzeit. – Matthiesen Verlag, 2015. – 532 S. - Grygorieva, Tetiana (Наукові записки НаУКМА. Історичні науки, 2018)
The dissertation-based monograph by Paul Srodecki suggests an impressive research of the Antemurale rhetoric, in particular the way it crystallized and functioned in Europe mostly from the 12th to the 17th century. The Author explores rhetorical clichés and strategies to demonstrate how particular concepts shaped and transformed propagandistic discourse; which of them found the most welcoming reception and, thus, were transferred across borders; and which ones were the specific instruments and media of this transfer. In the Introduction, the Author points out that contemporary bulwark rhetoric, which is extensively used in political discourse to characterize both the extended European borders and current geopolitical conflicts in Europe, actually finds its origin in Middle Ages, when European unity presented itself in the form of Respublica Christiana. The particular virtue of the monograph is an extensive and complex use of the Eastern European sources (Czech, Polish, Hungarian), which still find limited attention in Western European and Northern American scholarship with focus on the propagandistic uses of the phenomenon of the “Other”. In this way, Paul Srodecki made his personal contribution into welcoming new members of the European Union after its enlargement in 2004, which is the point where he starts his narrative.